2018
DOI: 10.1111/fare.12317
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Father Engagement for Nonresident Fathers

Abstract: Objective To develop reliable and valid measures of nonresident father engagement. Background Although engagement measures exist for resident fathers, they have not been validated for nonresident fathers. Without valid and reliable measures, research on and programs for these fathers are limited in their ability to capture this salient dimension of fathering. Method From a focus group of 71 nonresident biological fathers, father–child engagement scales were created. Separate scales were created for fathers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Researchers who employ survey techniques, and those who design large‐scale survey data collections, should take care to use measures of fathering and related constructs (e.g., coparenting and maternal gatekeeping) with strong psychometric properties. In particular, the past decade has seen the development of more sophisticated measures of nonresident fathering that capture multiple dimensions of father involvement (i.e., engagement, accessibility, responsibility) with distinct versions for fathers of children of various ages (Dyer, Kauffman, Fagan, Pearson, & Cabrera, ; Fagan, Dyer, Kaufman, & Pearson, ). Fagan, Kaufman, and Dyer () found that measuring nonresidential fathers' telephone and social media contact is as important as measuring face‐to‐face contact.…”
Section: Persistent Challenges and Directions For Future Researchmentioning
confidence: 99%
“…Researchers who employ survey techniques, and those who design large‐scale survey data collections, should take care to use measures of fathering and related constructs (e.g., coparenting and maternal gatekeeping) with strong psychometric properties. In particular, the past decade has seen the development of more sophisticated measures of nonresident fathering that capture multiple dimensions of father involvement (i.e., engagement, accessibility, responsibility) with distinct versions for fathers of children of various ages (Dyer, Kauffman, Fagan, Pearson, & Cabrera, ; Fagan, Dyer, Kaufman, & Pearson, ). Fagan, Kaufman, and Dyer () found that measuring nonresidential fathers' telephone and social media contact is as important as measuring face‐to‐face contact.…”
Section: Persistent Challenges and Directions For Future Researchmentioning
confidence: 99%
“…Preschool‐age children from low‐income families are at risk for compromised development (Lengua et al, 2007) in these areas, which are implicated in longitudinal trajectories of social–emotional development (Shaw et al, 2003). Identifying specific family‐based pathways conferring developmental risks provides key information for researchers and practitioners, especially when this research takes a whole family perspective and includes fathers (Cabrera et al, 2014; Dyer et al, 2018).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…They will rate their own Hostile/reactive parenting using the hostile/reactive parenting subscale of the PACOTIS, which measures parents’ and caregivers’ responses to difficult behavior in young children. Fathers/caregivers will rate their level of Engagement with the child using the FRPN Father Engagement scale [ 43 ].…”
Section: Methodsmentioning
confidence: 99%